Hypertension and Abdominal Aortic Aneurysms: Risk Factors, Diagnosis, and Endovascular Treatment - Diogo Melo, Laura; Flávia Bragança Rabelo de Sousa; Priscilla Francielle de Souza; Nayara Christini Anselmo; Amanda Lacerda Amaral (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Hypertension is a chronic condition characterized by persistently elevated blood pressure, which significantly contributes to cardiovascular morbidity and mortality. When not properly controlled, it can lead to severe complications, including abdominal aortic aneurysms, a pathological dilation of the arterial wall that may result in rupture and sudden death. The interaction between hypertension and abdominal aortic aneurysms has been extensively studied, highlighting that hypertension is a crucial risk factor for the development and growth of these aneurysms. The therapeutic approach for these patients involves monitoring and treatment strategies, with endovascular treatment emerging as an effective minimally invasive option. Objective: The systematic literature review aimed to assess the risk factors associated with hypertension and abdominal aortic aneurysms, as well as to examine the diagnostic methods and the effectiveness of endovascular treatment for this condition. Methodology: The methodology was based on the PRISMA checklist and included an extensive search in the databases PubMed, Scielo, and Web of Science. The descriptors used were "hypertension," "abdominal aortic aneurysm," "endovascular treatment," "aneurysm diagnosis," and "cardiovascular risk factors" to find relevant articles. Studies published in the last 10 years that addressed clinical, diagnostic, and therapeutic aspects related to the topic were included. The inclusion criteria were: clinical studies, systematic reviews, and randomized controlled trials; publications in peer-reviewed journals; and studies involving adult patients with a diagnosis of hypertension and abdominal aortic aneurysm. The exclusion criteria were: studies that did not specifically address abdominal aortic aneurysms; articles outside the scope of endovascular treatment; and publications older than a decade. Results: The results showed that hypertension is a predominant risk factor for the development and growth of abdominal aortic aneurysms. Early diagnosis through imaging techniques, such as ultrasound and computed tomography, was crucial for managing the condition. Endovascular treatment was highlighted as an effective approach, offering advantages over open surgery, such as shorter recovery time and fewer complications. Studies indicated that regular monitoring and early intervention are essential for reducing mortality associated with abdominal aortic aneurysms. Conclusion: In conclusion, hypertension plays a significant role in the development and progression of abdominal aortic aneurysms. Early diagnosis and the choice of endovascular treatment have been shown to improve clinical outcomes and reduce mortality. Endovascular treatment represents a viable and less invasive alternative compared to traditional surgery, proving to be an important approach in managing patients with abdominal aortic aneurysms associated with hypertension.